THE IMPORTANCE OF THE NUTRICIONAL APPROACH IN THE TREATMENT OF DEPRESSION - Kelly de Jesus Cordeiro Oliveira, Letícia; Cláudio Gagliardo, Luiz (Health and Society, 2023)
Depressive disorders are a serious public health problem due to their high prevalence, general health repercussions and psychosocial impact, and are one of the main causes of disability in the world, limiting physical, personal and social functioning. These disorders are caused as a result of failures in the communication of neurotransmitters with the Nervous System, which act in psychomotor activities, appetite, sleep and mood. The treatment applied to patients with depression usually combines psychotherapy and pharmacological therapy, however, nutritional therapy is not usually an option to be added to traditional treatment yet, but more and more studies have been published that emphasize the possibility of alternative treatments and / or complementary, based on nutrition, thus, the question arises about why nutritional therapy is still little used in the control of depression and associated symptoms and the importance of its execution for an adequate recovery of the health state. The general objective of this work was to understand clearly the impact that nutritional therapy consists of in the control of symptoms of depression, in addition to finding ways to avoid them, as it deals with a disease with a high incidence today, especially during the course of the disease. pandemic, depression is a topic that must be treated in detail, clearly and concisely pointing out its common symptoms and effective ways to control them. The present study is a project for a narrative review to be developed in the Course Completion Work, carried out from January to December 2022, through a systematic literature review about the influence of nutrition science in the treatment and control of the disorder depressive.